2000
DOI: 10.1034/j.1399-3003.2000.15d18.x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilaginous airway wall dimensions and airway resistance in cystic fibrosis lungs

Abstract: It is not clear how airway pathology relates to the severity of airflow obstruction and increased bronchial responsiveness in cystic fibrosis (CF) patients. The aim of this study was to measure the airway dimensions of CF patients and to estimate the importance of these dimensions to airway resistance using a computational model.Airway dimensions were measured in lungs obtained from CF patients who had undergone lung transplantation (n=12), lobectomy (n=1), or autopsy (n=4). These dimensions were compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 43 publications
2
68
0
Order By: Relevance
“…The characteristic airway abnormalities are bronchiectasis, thickening of the airway wall and mucus plugging [97,103,107,[120][121][122][123][124][125][126], as shown in figure 5.…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic airway abnormalities are bronchiectasis, thickening of the airway wall and mucus plugging [97,103,107,[120][121][122][123][124][125][126], as shown in figure 5.…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
“…Airway disease in CF is characterised by mucus plugging, chronic infection and an excessive inflammatory response, leading to peripheral airway changes in the first few months of life [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. The characteristic airway abnormalities are bronchiectasis, thickening of the airway wall and mucus plugging [97,103,107,[120][121][122][123][124][125][126], as shown in figure 5.…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
“…The structural alterations characterising the CF airways include goblet cell and submucosal gland extension to bronchioles and greater height of the epithelium. Loss of cartilage [55], excessive angiogenesis [56] and increased thickness of inner wall and smooth muscle areas in peripheral airways is also observed [57]. A dense fibrous deposition of collagens I and III, tenascin and elastin is reported in the bronchial wall [58].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…(Tiddens HA, et al, 2000) Changes in the airway dimensions of CF patients compared to chronic obstructive lung disease (COPD) patients showed that, for airways of 1.9 mm diameter (12 th generation), there was an approximately fivefold increase in the smooth muscle area and a threefold increase in the inner wall area without epithelium. In the larger airways (35 mm diameter) there was a 1.5 increase in smooth muscle area with an almost identical inner wall area without epithelium.…”
Section: Respiratory Physiological Changes In Cfmentioning
confidence: 99%
“…(Goldman et al, 1997;Rosenstein & Zeitlin, 1998). Thus in CF, bacterial colonization and mucus hypersecretion occur as a consequence, leading to progressive lung damage (Tiddens et al, 2000) Fig. 8.…”
Section: Mucus and Mucociliary Clearance In Cfmentioning
confidence: 99%